Kenya - Economic Development, Police Oversight, and Accountability : Linkages and Reform Issues - World Bank (World Bank, 2012)
The objective of this study is to contribute to the ongoing dialogue on police reform in Kenya, where poor police services are eroding the state's capacity to protect people and property, thereby limiting the country's efforts in relation to economic development and poverty reduction. Five years after launching a series of programs and pilot projects to improve police performance, the government of Kenya concluded that the reform program achieved only limited success: the country is continuing to experience high levels of crime and inter-ethnic violence and other insecurity concerns. Since 2003, reforms have focused on addressing the chronic lack of public confidence in the police and the persistence of corruption at all levels of the police force. Many of the reforms have been aimed at enhancing operational efficiency and expanding institutional capacity, especially by rehabilitating premises and purchasing vehicles. Despite these efforts, the force continues to be seriously weakened by structural dysfunction and extremely limited capacity, which are at the center of the most serious governance problems facing Kenya, namely, large-scale corruption, high levels of crime, and interethnic violence. This study supplements the Kenyan experience by drawing on police reform research and experiences from Latin America and elsewhere in Sub-Saharan Africa.